THE PERSONALITY OF MAIN CHARACTER IN THE FILM SERIES NOBUTA WO PRODUCE BY IZUMI KIZARA (A CARL GUSTAV JUNG’S PSYCHOANALYTIC APPROACH) - Nuriman, Nurfitiani; Emzir, Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2018)
This research aimed to obtain a deep depiction of personality type on the main character in the film series: Nobuta wo Produce by Izumi Kizara. Film series Nobuta wo Produce is a television drama series adapted from novel with the same title by Gen Shiraiwa. This research was conducted using content analysis method. This research data was analyzed through psychoanalytic by Carl Gustav Jung approach. The data were collected through documents, and data observations about the main character personality in film series: Nobuta wo Produce by Izumi Kizara. The result showed that Kiritani Shuuji as the main character of film series: Nobuta wo Produce by Izumi Kizara has two tendencies of the dominant personality type, thinking introvert type and feeling ekstravert type. The result lead to recommendation to Japanese literature educator, literature researcher, film review, and parents.